NMDA receptor antagonists mitigate COVID-19-induced neuroinflammation and improve survival in a mouse model - Emily R. Prantzalos; Jane P. Chesser; Judy Songrady Logan; Kristen A. McLaurin; Charles D. Anderson; Jon D. Gabbard; William E. Severson; Kenneth E. Palmer; Bobbi Jo Mullins; Linda Dwoskin; Jill R. Turner (Scientific Reports)
Abstract The virus known to cause COVID-19, SARS-CoV-2, exhibits severe and complex neurological symptoms. These effects may be attributed to a virus-induced neuroinflammatory environment, warranting exploration of the respiratory centers of the brain, namely the pons and medulla, specifically in relation to neuroinflammation, demyelination, and neuronal death in response to COVID-19. Interestingly, older adults with neurological dysfunction maintained on N-methyl-d-aspartate receptor (NMDAR) antagonists, such as memantine, had reduced incidence and severity of COVID-19. Thus, the present study aimed to evaluate (1) the neuroinflammatory response to COVID-19 in the respiratory centers of the brain, and (2) to assess the extent to which NMDAR antagonists offer neuroprotective measures in the context of COVID-19. In a susceptible mouse model, animals inoculated with SARS-CoV-2 were pre-treated with either memantine or an alternative NMDAR antagonist, ifenprodil. Inoculated animals had poor survival and showed signs of neuroinflammation, evidenced by a reduction in morphological structure, demyelination, and changes in astrocyte and microglial expression in the pons and medulla. Mice pre-treated with memantine showed improved survival when challenged with COVID-19 and a reduction in virus-induced neuroinflammatory impairments. Our findings support the further investigation of memantine for the prevention of COVID-19 induced neuroinflammation and resultant neurological symptoms and shed light on the possible protective mechanism of memantine in the elderly maintained on NMDAR antagonists.